An overview and methodological assessment of systematic reviews and meta-analyses of enhanced recovery programmes in colorectal surgery. Issue 5 (30th May 2014) - Chambers, Duncan; Paton, Fiona; Wilson, Paul; Eastwood, Alison; Craig, Dawn; Fox, Dave; Jayne, David; McGinnes, Erika
Abstract : Objectives: To identify and critically assess the extent to which systematic reviews of enhanced recovery programmes for patients undergoing colorectal surgery differ in their methodology and reported estimates of effect. Design: Review of published systematic reviews. We searched the Cochrane Database of Systematic Reviews, the Database of Abstracts of Reviews of Effects (DARE) and Health Technology Assessment (HTA) Database from 1990 to March 2013. Systematic reviews of enhanced recovery programmes for patients undergoing colorectal surgery were eligible for inclusion. Primary and secondary outcome measures: The primary outcome was length of hospital stay. We assessed changes in pooled estimates of treatment effect over time and how these might have been influenced by decisions taken by researchers as well as by the availability of new trials. The quality of systematic reviews was assessed using the Centre for Reviews and Dissemination (CRD) DARE critical appraisal process. Results: 10 systematic reviews were included. Systematic reviews of randomised controlled trials have consistently shown a reduction in length of hospital stay with enhanced recovery compared with traditional care. The estimated effect tended to increase from 2006 to 2010 as more trials were published but has not altered significantly in the most recent review, despite the inclusion of several unique trials. The best estimate appears to be an average reduction of around 2.5 days in primary postoperative length of stay. Differences between reviews reflected differences in interpretation of inclusion criteria, searching and analytical methods or software. Conclusions: Systematic reviews of enhanced recovery programmes show a high level of research waste, with multiple reviews covering identical or very similar groups of trials. Where multiple reviews exist on a topic, interpretation may require careful attention to apparently minor differences between reviews. Researchers can help readers by acknowledging existing reviews and through clear reporting of key decisions, especially on inclusion/exclusion and on statistical pooling.